The politics of refugees in South Asia identity, resistance, manipulation - Murshid, Navine (Routledge advances in South Asian studies, 2014)
This text offers a novel approach to studying the political impact of refugees. It centres on the political incentives and reactions that arise in countries from hosting refugees.